Dynamic response of a pile embedded into a layered soil. Issue 87 (August 2016) - Martinelli, Mario; Burghignoli, Alberto; Callisto, Luigi
Abstract: This paper studies the seismic response of a foundation pile embedded in a saturated coarse-grained deposit. The pile response is examined through a series of three-dimensional dynamic finite element analyses incorporating an advanced plasticity soil model and implementing a fully coupled interaction between the soil skeleton and the pore fluid. The study is mainly focused on the development of the internal forces in a pile immersed into a deposit including two soil layers with a different stiffness, and accounts for the development of excess pore water pressures during the seismic motion. The effects of the initial porosity and of the permeability of the soil layers are investigated, together with the effects of changing the pile length, the pile diameter, and the boundary condition at the top of the pile. Finally, the results of the finite element simulations are used as a benchmark to evaluate the capability of a number of simplified predictive methods and to provide guidance for their implementation. Highlights: Seismic response of a pile immersed in saturated coarse-grained deposit is studied. Fully coupled 3D dynamic FEM analyses performed with advanced soil model. Effect of initial porosity, permeability, pile length and diameter are investigated. Profound effect of generation of excess pore pressures on internal forces in pile. In some cases, simplified procedures are able to predict maximum bending moments.